2017
DOI: 10.13189/ujer.2017.050410
|View full text |Cite
|
Sign up to set email alerts
|

CHAID Analysis to Determine Socioeconomic Variables that Explain Students' Academic Success

Abstract: This study aims to determine students' characteristics that predict their academic success. The study group consisted of 4229 students studying at middle schools in Burdur. The data were collected using a questionnaire in the 2014-2015 academic year and analyzed using CHAID (Chi-squared Automatic Interaction Detection) analysis, a type of decision-tree technique. The CHAID analysis was completed with 10 branches and 18 nodes, and indicated that students' academic success (end-year success grade) was explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
1
Order By: Relevance
“…Then we used a decision tree analysis; CHAID (Chi-squared Automatic Interaction Detection analysis) to investigate exercisers' characteristics that may predict exercise dependence. The CHAID analysis is used to investigate associations between predictors (in the present study; anxiety, obsessive passion and appearance orientation) and the outcome variable (in the present study; exercise dependence) by searching for the predictors that differ the most on the outcome variable (Önder & Uyar, 2017). The variable that best explains the dependent variable is selected and, according to the selected variable, the data is classified into subgroups.…”
Section: Analysesmentioning
confidence: 99%
“…Then we used a decision tree analysis; CHAID (Chi-squared Automatic Interaction Detection analysis) to investigate exercisers' characteristics that may predict exercise dependence. The CHAID analysis is used to investigate associations between predictors (in the present study; anxiety, obsessive passion and appearance orientation) and the outcome variable (in the present study; exercise dependence) by searching for the predictors that differ the most on the outcome variable (Önder & Uyar, 2017). The variable that best explains the dependent variable is selected and, according to the selected variable, the data is classified into subgroups.…”
Section: Analysesmentioning
confidence: 99%
“…The cut-off point of continuous variable stratification is determined by CHAID decision tree analysis, using a = 0.05 as the test level. The variables are further stratified until p > 0.05 [18]. In this study, the analysis results showed that age of >70 years old and fibrinogen level of >4 g/L had a greater impact on the prognosis of ASO patients.…”
Section: Discussionmentioning
confidence: 71%
“…Under our conditions, we found a significant pattern of teacher preferences when performing their pedagogical actions. The robustness of our classification model relies on both the criteria of the exhaustive CHAID analysis performed ( Önder and Uyar, 2017 ; Feu et al, 2019 ; Rodríguez-Sabiote et al, 2021 ) and on the very low Bonferroni-adjusted p -values obtained in the analysis, which are a measure of the compatibility of the entire model of data analysis with the structure of the collected data ( Greenland et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%